Impact of organizational justice on citizenship behavior: Mediating role of faculty trust - Nosheena Tahseen; Muhammad Saeed Akhtar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The purpose of the study was to explore the mediating role of faculty trust in the relationship between organizational justice and teachers' citizenship behavior in university teacher-education faculties in the Punjab province of Pakistan. The participants of the study were teacher-educators (lecturers, assistant professors, associate professors, professors) teaching at the Education Faculties of twelve universities (eight in public and four in the private sector) offering at least master's degree program in Education. The strategy for selecting sample was stratified proportionate random sampling. The instruments of data collection were adapted for the study based on Organizational Justice Scale by Niehoff and Moorman (1993), Faculty Trust Scale by Hoy and Tschannen-Moran (2003), and Organizational Citizenship Behavior Scale by Podsakoff et al. (1990). The proposed model was then tested through mediation analysis. The results indicated that the effect of organizational justice on organizational citizenship behavior was significantly mediated through faculty trust. The finding implies that positive perception of organizational justice not only strengthens faculty trust, but this fortified trust also stimulates teachers' citizenship behavior. It also signifies the value of justice in an educational organization.
Keywords: 330; organizational justice; faculty trust; organizational citizenship behavior; teacher-education